The Life-cycle of biosteres persulcatus with reference to adults' reproductive capacity on eggs of Carambola fruit-fly - A. G., Ibrahim; I. P., Palacio; Ibrahim, Rohani (Universiti Putra Malaysia Press, 1993)
A study of the life-cycle of Biosteres persulcatus Silvestri, a larval parasitoid of (Bactrocera (B) sp. near Bactrocera dorsalis A), was conducted in the laboratory (26.50C± 1.50 C). There are 4 larval stages as indicated by the sizes of the mouthhooks. The first larval moult occurred in the newly{ormed puparium of the host. The entire developmental period from egg to adult emergence for male and female was 16.3± 0.80 days and 1 7.1 ± 0.80 days respectively. The average reproductive capacity during the life span was 67 ± 3.5 eggs.